2019
DOI: 10.3390/molecules24081582
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective Effect of Walnut Oligopeptides Against Gamma Radiation-Induced Splenocyte Apoptosis and Intestinal Injury in Mice

Abstract: Walnut oligopeptides (WOPs) intake is associated with the augment of the antioxidant defense system and immune system. The chief object of this study is to evaluate the radioprotective effect of walnut oligopeptides extracted from walnut seed protein against 60Coγ-irradiation induced damage in mice. Female BALB/c mice were administered WOPs through drinking water for 14 days until a single dose of whole-body 60Coγ-irradiation. The 30-day survival test was carried out in the first group (8 Gy), and the other tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 47 publications
6
19
0
Order By: Relevance
“…However, no significant difference was found in the whey protein group or omeprazole group when compared with the ethanol group. Notably, administration with WOPs reduced the expression of NF-κB p65, Bax, and caspase 3, and increased the expression of IκBα and Bcl 2 in comparison with those of ethanol rats, which was consistent with previously reported studies, showing WOPs could inhibit IR-induced splenocyte apoptosis and inflammation [23]. Moreover, comparing the gastroprotective effects of WOPs and omeprazole or whey protein, WOPs were superior in the regulation of anti-apoptosis protein Bcl-2 in comparison with omeprazole group, but there was no significant difference between both groups on NF-κB p65, Bax, and caspase-3 expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, no significant difference was found in the whey protein group or omeprazole group when compared with the ethanol group. Notably, administration with WOPs reduced the expression of NF-κB p65, Bax, and caspase 3, and increased the expression of IκBα and Bcl 2 in comparison with those of ethanol rats, which was consistent with previously reported studies, showing WOPs could inhibit IR-induced splenocyte apoptosis and inflammation [23]. Moreover, comparing the gastroprotective effects of WOPs and omeprazole or whey protein, WOPs were superior in the regulation of anti-apoptosis protein Bcl-2 in comparison with omeprazole group, but there was no significant difference between both groups on NF-κB p65, Bax, and caspase-3 expression.…”
Section: Discussionsupporting
confidence: 92%
“…Nowadays, natural products, especially food-derived peptides, have gradually attracted researchers' attention because of its varied biological effects with reduced side effects [33,34]. WOPs, which are mainly composed of small-molecule oligopeptides derived from walnuts (Juglans regia L.), have been reported to have various physiological functions such as anti-oxidants, anti-inflammatory, anti-fatigue, and attenuating irradiation-induced hematopoietic [22,23]. However, the effects of WOPs on ethanol-induced gastric mucosal injury has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The AM, NC, and YM groups were administered distilled water. The drinking feeding mode was a gentle feeding mode for elderly mice, whose strict quality control and accuracy were confirmed by our team with solid results in earlier reports [ 41 , 42 ].…”
Section: Methodssupporting
confidence: 77%
“…Antioxidants are found naturally in several vegetables and fruits (Shaban et al., 2017 ). Since we are exposed to gamma ray frequently in daily life, it is of utmost importance to develop active and safe radio protectors (Zhu et al., 2019 ). Phytochemicals observed in plants and foods lacking toxicity have drawn significant attention (Cheng et al., 2019 ), as against synthetic compounds (Deng et al., 2019 ).…”
Section: Role Of Antioxidant Against Gamma Radiationmentioning
confidence: 99%
“…Earlier research works have indicated that IR can trigger enormous slaying of blood cells like lymphocytes and ceasing of the propagation of hematopoietic progenitors, thus causing overpowering of immune function (Zhao et al., 2014 ). It can also have a negative impact on antioxidant system resulting in reduced glutathione level and activity of antioxidant enzymes (Zhu et al., 2019 ), as well as attack intestinal stem cells which results in intestinal epithelium damage, disruption of intestinal barrier function (He et al., 2017 ), damage of bone‐marrow progenitor cells and gastrointestinal epithelium (Frisby et al., 2007 ), decrease in small intestine monoamines level—dopamine, epinephrine, norepinephrine, and serotonin (Lu et al., 2016 ). It is vital to protect the biological systems from lethality or genotoxicity induced by radiation.…”
Section: Introductionmentioning
confidence: 99%